Advanced IT Systems Limited: Case of Ethics and Conflicts of Interest. Issue 1 (March 2020) - Patanjali, S.; Gupta, Pooja
Advanced IT Systems Limited (AISL) was a family-owned software solutions and services company based in Mumbai, and was in business for about 10 years. The chief executive officer (CEO) had ambitions of growing the company into one of the large Indian IT companies. Apart from concentrating on the business growth, the CEO with the help of his HR head introduced several people-oriented policies and hoped that these would lay a good base for further growth of the company. The case describes a conflict of interest that got exposed when one particular business head was championing a young computer science graduate for nomination as a high potential and accelerated promotion but kept hidden that he was in a personal relationship with the lady. Should such a relationship come in the way of the career progression of an individual who was otherwise talented and deserved the promotion? The case covers issues of the setting of corporate ethical and cultural standards, leadership and decision-making, policy and pragmatism, and of meeting client needs and organizational propriety.